THE EFFECT OF USING FLASHCARD MEDIA ON STUDENTS’ VOCABULARY MASTERY - Suki Mariana Waruwu (JURNAL LINER (Language Intelligence and Educational Research), 2020)
The purpose of this research are to find out: 1) The application of flashcard media in teaching vocabulary. 2) Students’ vocabulary mastery before and after using flashcard media. 3) Whether there is a significant effect of using flashcard media at the seventh grade students of SMP Swasta Sariputra. Method of the research is experimental. The population of this research are all of the Seventh grade students of SMP Swasta Sariputra that consists of 62 students. Systematic sampling technique is used to get the sample of research , the sample consist of 31 students. The technique for collecting data are observation sheet and test. The result of the application of flashcard media is 3.5 categorized “Very Good”. Before using flashcard media is 40.09 categorized “Fail”. Meanwhile, after using flashcard media is 63.11 categorized “Enough”. The result of ttest 3.75 and ttable 2.04 it means that there is a significant effect of using flashcard media on students’ vocabulary mastery at the seventh grade students of SMP Swasta Sariputra in 2018/2019 Academic Year.